Development and process parameter optimization with an integrated test bench for rolling and forming strips of oolong tea. (5th October 2021) - Jia, Jiangming; Zhang, Chenan; Yuan, Bin; Chen, Zhiwei; Chen, Jianneng
Abstract : To solve the problems associated with the low rate of single‐use tea formation in oolong tea rolling equipment and the need for multiple rolling and formation processes, a new rolling and formation process is proposed. Based on the traditional rolling process, a heavy pressure holding process is added to keep the tea in a tight and curved state after the rolling is completed. Based on the traditional 25‐type rolling machine, the overall structure design of a test bench with integrated rolling and formation is described, and the control system of the test bench is established. In this article, a new orthogonal experiment using 12 factors and 3 levels for the rolling and formation of oolong tea strips is conducted, and the optimal process parameters are obtained. The experiment is carried out under the optimum process parameters, and the experimental results show that the strip formation rate of oolong tea is 77.37%, the tea breakage rate is 3.73%, and the time efficiency is 1.062 g s −1 . Compared with the traditional rolling process, the formation rate and time efficiency of this process are significantly improved, and the comprehensive score is 1.613 times higher than that of the traditional rolling process. This shows that the new rolling and formation process improves the strip formation rate and efficiency of oolong tea production to ensure tea quality. Practical Applications: Oolong tea is popular because of its high medicinal value and lasting fragrance. Efficient rolling and forming equipment can improve the efficiency of oolong tea production. The optimal parameters also provide a reference for rolling and forming equipment. Abstract : A new rolling and formation process was proposed by designing a test bench and a new orthogonal experiment. The new rolling and formation process improved the strip formation rate and efficiency of oolong tea production to ensure tea quality.